Application of Wakālah bi al-Ujrah Contract in Letter of Credit (L/C) Services in Islamic Banking - Liswardi (Journal of Economicate Studies, 2018)
The rapid expansion of Islamic banking has led to the development of various financial instruments that extend beyond traditional fund mobilization. Among these is wakālah bi al-ujrah, a fee-based agency contract whereby a bank is appointed to perform specific services on behalf of a client for a predetermined fee. A prominent application is in the issuance and administration of Letters of Credit (L/C), which enable sharia-compliant international trade. This study investigates the theoretical underpinnings, legal foundation, and practical application of wak?lah bi al-ujrah within L/C services in Islamic banking. Utilizing a qualitative-descriptive method, the research draws on classical Islamic legal texts, national fatwas, and actual banking practices to evaluate the legitimacy and operational framework of the contract. The findings indicate that wak?lah bi al-ujrah is consistent with classical jurisprudence and fulfills the regulatory and ethical standards necessary for modern Islamic financial services.